(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Nowadays, the incidence, mortality, and disability rates associated with cerebrovascular diseases (CVDs) continue to rise globally, making this issue increasingly urgent. According to literature data, the incidence of CVDs is approximately 2.5 per 1,000 people. In Uzbekistan, post-stroke disability rates are estimated at 3.2 per 10,000 individuals. Given the broad spectrum of dysfunctions caused by CVDs — particularly cognitive impairments — it is crucial to ensure timely and effective treatment approaches. In recent years, innovative methods aimed at improving cognitive functions have emerged. One of the most promising techniques is Neurofeedback, a novel neurotherapy approach recently introduced in Uzbekistan. However, its efficacy in treating neurological conditions remains underexplored in the local context. Considering these factors, studying this method in patients with cerebrovascular diseases is highly relevant.